1989
DOI: 10.1159/000116366
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive Substance P and Somatostatin in the Cerebrospinal Fluid of Senile Parkinsonian Patients

Abstract: The concentration of substance-P-like immunoreactivity (SPLI) and somatostatin-like immunoreactivity (SLI) in the lumbar spinal fluid of senile parkinsonian patients (mean age 77.6 ± 6.7 years) and senile control patients (mean age 83.5 ± 5.6 years) were determined by specific radioimmunoassays. Mean SPLI and SLI levels in the control group were 8.1 ± 2.0 (SD) and 32.5 ± 12.0 fmol/ml, respectively. The mean SPLI levels were not significantly different in the groups. The mean SLI level was significantly lower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Decreased levels of somatostatin have been found in CSF of parkinsonian patients [27] compared with AD patients and elderly controls, which is in accordance with our data. In another proteomics study, CSF neuronal cell adhesion molecule was found to be decreased in PD compared with healthy controls [23].…”
Section: Neuronal/synaptic Proteinssupporting
confidence: 92%
“…Decreased levels of somatostatin have been found in CSF of parkinsonian patients [27] compared with AD patients and elderly controls, which is in accordance with our data. In another proteomics study, CSF neuronal cell adhesion molecule was found to be decreased in PD compared with healthy controls [23].…”
Section: Neuronal/synaptic Proteinssupporting
confidence: 92%
“…MJD is believed to be caused by a CAG expansion in the SCA3 gene located on chromosome 14q32.1 and is characterized by poor motor control. Based on previous anatomic, biochemical, and pharmacological studies associating SP with dopaminergic neurons in the substantia nigra and the striatum [6264], Matsuishi and colleagues conducted a study comparing the CSF SP levels of 7 subjects with MJD to 14 controls. They found that the level of SP within the CSF of patients with MJD was significantly lower than the levels observed in the control patients.…”
Section: Tachykinins and Central Nervous System Disordersmentioning
confidence: 99%
“…In the past decade, the reduced levels of central somatostatin in Alzheimer's disease, Huntington's disease, and other degenerative diseases had been reported (Beal et al, 1987(Beal et al, , 1988Cramer et al, 1989). However, up to now the change of somatostatin concentration in epilepsy is controversial.…”
Section: Introductionmentioning
confidence: 99%